Efficacy of the Synergy Between Live-Attenuated and Inactivated PRRSV Vaccines Against a NADC30-Like Strain of Porcine Reproductive and Respiratory Syndrome Virus in 4-Week Piglets - Li, Chaosi; Liu, Zhicheng; Chen, Kai; Qian, Jie; Hu, Yulong; Fang, Shuhe; Sun, Zhi; Zhang, Chunhong; Huang, Lv; Zhang, Jianfeng; Huang, Nian (Frontiers in Veterinary Science, 2022)
The NADC30-like strain of porcine reproductive and respiratory syndrome virus (PRRSV) is a novel strain responsible for substantial economic losses to swine production in China. This study evaluated the cross-protective efficacy of the synergy between live-attenuated and inactivated PRRSV vaccines compared with a single vaccination with PRRS modified-live virus (MLV) vaccine against challenge with NADC30-like strain, v2016/ZJ/09-03. A total of 45 PRRSV free pigs were randomly divided into five groups: (1) strict control (SC); (2) positive control (PC); (3) single MLV dose (M1); (4) primed intramuscularly with MLV and boosted with killed vaccine 3 weeks later (MK1); and (5) intramuscular prime MLV boosted subcutaneously with killed vaccine B 3 weeks later (MK2). Serological tests in MK groups revealed no differences in both anti-N and anti-GP protein antibodies compared with M1 group, and failed to provide further protection against clinical signs, virus shedding, and gross lesions. However, the viremic titer, gross lung lesions, and average daily weight gain were significantly improved in the MLV vaccinated groups, suggesting that MLV provides substantial cross-protection against the NADC30-like virus. Thus, as a booster, the killed vaccine confers minimal additional protection in NADC30-like infected piglets.